The Influence of Christian Religious Education on the Development of Ethics and Morals Among Generation - Elisabeth Sitepu (PT. Anagata Sembagi Education, 2026)
This article examines the influence of Christian Religious Education (CRE) on the development of ethics and morals among Generation Z, a cohort raised amid pervasive digital connectivity and increasingly fluid value systems. Employing a qualitative descriptive method through systematic literature review, twenty-five peer-reviewed sources published mainly between 2021 and 2026 were analyzed to identify recurring themes linking religious instruction, family and church involvement, and moral outcomes. The review finds that CRE functions not merely as doctrinal transmission but as a holistic formation process integrating cognitive understanding of biblical values, relational modeling by parents and teachers, and spiritual practice that together strengthen ethical reasoning and self-regulation. Digital exposure emerges as both a risk multiplier for moral drift and a potential channel for values-based catechesis when intentionally utilized. The novelty of this study lies in synthesizing theological-pedagogical and digital-sociological perspectives into an integrated framework explaining how CRE mediates Generation Z's ethical development within triadic family-church-school ecosystems. Findings suggest that dialogical, participatory CRE pedagogy combined with consistent value reinforcement across social institutions produces more durable moral character than instruction confined to formal classroom settings alone, offering practical implications for churches, schools, and families.